2010
DOI: 10.1007/s10120-010-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of S-1 monotherapy in elderly patients with advanced gastric cancer

Abstract: cancer is the most frequently encountered malignancy and the second leading cause of cancer-related death [3]. The prognosis of unresectable or recurrent tumors is very poor: the median survival time is about 4 months with best supportive care [4][5][6]. Although several randomized trials of treatments for advanced gastric cancer were conducted during the 1990s, with anthracyclines, mitomycin C, 5-fl uorouracil (5-FU), methotrexate, and cisplatin [7][8][9][10][11][12][13][14][15], no standard treatment for adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…The conventional schedule of S-1 administration was employed in the two studies. Since the present study comprised no patients with gastrectomy, we referred to the results reported by Tsushima et al (20). These results suggest that age is likely to affect RDI in the conventional S-1 schedule in NSCLC.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The conventional schedule of S-1 administration was employed in the two studies. Since the present study comprised no patients with gastrectomy, we referred to the results reported by Tsushima et al (20). These results suggest that age is likely to affect RDI in the conventional S-1 schedule in NSCLC.…”
Section: Discussionmentioning
confidence: 63%
“…Aoyama et al (19) reported that in gastric cancer no difference was observed in the RDI of the adjuvant chemotherapy with S-1 in older (≥70 years old) and younger (<70 years old) patients with gastrectomy. However, Tsushima et al (20) demonstrated that median RDI in younger (≤65 years old) patients was likely to be lower compared to older (>65 years old) patients, including patients with unresectable gastric cancer. The conventional schedule of S-1 administration was employed in the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Nevertheless, S-1 alone can be used safely for the elderly and poor PS patients, which most stage IV patients are. 26,27 Neoadjuvant chemotherapy settings have been discussed lately to give an adequate amount of antitumor agent and if possible, downstage the non-curative tumor to perform R0 operation. The European group has reported recently that R0 surgery increased but did not affect overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of patients with advanced gastric cancer, Tsushima et al showed that S-1 monotherapy exhibited moderate efficacy in elderly patients (C76 years of age) and that these patients were at a higher risk of severe toxicities than the younger patients ( age B75 years). They recommended careful monitoring of toxicities in the elderly patients [6]. However, the safety and feasibility of adjuvant chemotherapy with S-1 in elderly patients has not been clarified.…”
Section: Introductionmentioning
confidence: 99%